Differences in Improving Student's Problem Solving Mathematics Ability Using Problem Based Learning and Discovery Learning - Yosephin Elisabeth Panggabean; Humuntal Banjarnahor; Mulyono Mulyono (Study Program of Mathematics Education of Unimed Postgraduate Program, 2023)
This study was carried out with the aim of determining whether the improvement in mathematical problem solving ability of students taught by the PBL learning model was higher than students that taught using the DL learning model. In this study, the population was all class XI science students at Markus High School Medan. The type of research used is quasi experimental research. The research samples were selected using purposive sampling techniques (selection of samples based on certain characteristics). Furthermore, randomization was carried out on the two classes selected to be designated as experimental class I and experimental class II. Class XI IPA 1 was selected as a PBL experiment class with 30 students and class XI IPA 2 was selected as a DL experimental class with 30 students. This study used the Anakova test. Based on the results of the study, it can be said that: Students who are taught using the PBL models are higher than students who are taught using the DL model with F_count > F_table shows that in student’s mathematical problem solving ability there are differences, is 5.936 > 4.01.